Analisis Nilai-nilai Kementerian Keuangan Berdasarkan Perspektif Agama-agama Abrahamik - Adhitama, Satria (Kamaya: Jurnal Ilmu Agama, 2024)
The Ministry of Finance of the Republic of Indonesia is one of the ministries that plays an important role in implementing state rights and obligations, especially in the field of state finance. There are five Ministry of Finance Values ​​that guide employees' attitudes and behavior, namely Integrity, Professionalism, Synergy, Service, and Perfection. It is necessary to strengthen the Values ​​of the Ministry of Finance among employees and officials of the Ministry of Finance so that every employee and official can apply the Values ​​of the Ministry of Finance, one of which is through understanding the Values ​​of the Ministry of Finance based on a religious perspective. This research aims to analyze the values ​​of the Ministry of Finance based on the perspective of religions, especially Abrahamic religions, such as Islam, Christianity, and Catholicism. The approach used in this research is a qualitative and descriptive approach. The data collection method uses in-depth interviews and literature study. The results of this research show that all the Ministry of Finance's values, including the main and accompanying behaviors, are found in Islamic, Christian, and Catholic religious teachings. There are many verses in the holy book Al-Quran and the Hadith of the Prophet Muhammad SAW which invite and oblige Muslims to have an attitude of integrity, professionalism, synergy, providing the best service, and achieving perfection. Likewise, in the Bible or Gospel, there are many verses that support the Values ​​of the Ministry of Finance and invite Christians to have an attitude of integrity, professionalism, synergy, service and perfection. It is hoped that this analysis of the Ministry of Finance's values ​​based on a religious perspective can be a means of strengthening the attitudes and behavior of Ministry of Finance employees.